2022
DOI: 10.1149/1945-7111/aca0c9
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopy to Study the Nucleation and Growth Phenomena in Liquid Electrolytes under Operando Conditions

Abstract: Scanning Electron Microscopy (SEM), while being amongst the most widespread analytical instrumentation, is not widely used to study nucleation and growth (NG) phenomena in liquids. This is, partially due to insufficient exposure of the electrochemical research community to its capabilities. Here, we report on a simple but versatile custom-made setup for liquid phase (LP) SEM to access chemically and electrochemically driven NG processes in liquids. In addition, we will reveal the experimental artifacts and lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…[2] In our case, the limited spatial and temporal resolution during the SEM imaging does not allow the evaluation of a possible area loss of the primary particles, whose dissolution rate has been reported to initially proceed rapidly by the reduction of the surface oxide layer. [4] It has also been reported that the dissolution of metallic Cu is slower than in cupric oxides, [30] and considering that we do not observe a noticeable change in the Cu nanocube morphology, we can conclude that the inevitable OCV-induced Cu NC oxidation is limited to a thin layer (i.e., not observable under the conditions used). In addition, the discernible redeposition of secondary particles, during the in situ SEM experiments at the cathodic potential of −1.1 V versus RHE, suggests that the simultaneous dissolution of the primary particles continues with a moderate amount of dissolved species, which is dependent on the applied, cathodic potential.…”
Section: Operando Co 2 Er Of Cu Ncs At −11 V Versus Rhesupporting
confidence: 65%
See 1 more Smart Citation
“…[2] In our case, the limited spatial and temporal resolution during the SEM imaging does not allow the evaluation of a possible area loss of the primary particles, whose dissolution rate has been reported to initially proceed rapidly by the reduction of the surface oxide layer. [4] It has also been reported that the dissolution of metallic Cu is slower than in cupric oxides, [30] and considering that we do not observe a noticeable change in the Cu nanocube morphology, we can conclude that the inevitable OCV-induced Cu NC oxidation is limited to a thin layer (i.e., not observable under the conditions used). In addition, the discernible redeposition of secondary particles, during the in situ SEM experiments at the cathodic potential of −1.1 V versus RHE, suggests that the simultaneous dissolution of the primary particles continues with a moderate amount of dissolved species, which is dependent on the applied, cathodic potential.…”
Section: Operando Co 2 Er Of Cu Ncs At −11 V Versus Rhesupporting
confidence: 65%
“…[2,3] At the same time, the need to bridge the scales for a better understanding of electrocatalytic phenomena has led to advancements in scanning EM instrumentation, which has also enabled the realization of electrochemical liquid-phase SEM (ec-LPSEM) experiments with valuable results. [4,5] In both cases, the challenging aspects of the techniques are similar; they mainly involve limitations in the spatial resolution, due to electron scattering caused by the presence of the liquid and the liquid-sealing membranes, and means of application of the potential, due to the geometrical and fabrication constraints of the substrate electrodes, which also contribute to the thickness of the cell. [6] Overall, there has been significant progress in controlling the liquid thickness and thus improving the spatial resolution of imaging samples in liquids.…”
Section: Introductionmentioning
confidence: 99%